Helicobacter pylori-induced NAT10 stabilizes MDM2 mRNA via RNA acetylation to facilitate gastric cancer progression - Deng, Min; Zhang, Long; Zheng, Wenying; Chen, Jiale; Du, Nan; Li, Meiqi; Chen, Weiqing; Huang, Yonghong; Zeng, Ning; Song, Yuanbin; Chen, Yongming (Journal of experimental & clinical cancer research, 2023)
N4-acetylcytidine (ac4C), a widespread modification in human mRNAs that is catalyzed by the N-acetyltransferase 10 (NAT10) enzyme, plays an important role in promoting mRNA stability and translation. However, the biological functions and regulatory mechanisms of NAT10-mediated ac4C were poorly defined. ac4C mRNA modification status and NAT10 expression levels were analyzed in gastric cancer (GC) samples and compared with the corresponding normal tissues. The biological role of NAT10-mediated ac4C and its upstream and downstream regulatory mechanisms were determined in vitro and in vivo. The therapeutic potential of targeting NAT10 in GC was further explored. Here, we demonstrated that both ac4C mRNA modification and its acetyltransferase NAT10 were increased in GC, and increased NAT10 expression was associated with disease progression and poor patient prognosis. Functionally, we found that NAT10 promoted cellular G2/M phase progression, proliferation and tumorigenicity of GC in an ac4C-depedent manner. Mechanistic analyses demonstrated that NAT10 mediated ac4C acetylation of MDM2 transcript and subsequently stabilized MDM2 mRNA, leading to its upregulation and p53 downregulation and thereby facilitating gastric carcinogenesis. In addition, Helicobacter pylori (Hp) infection contributed to NAT10 induction, causing MDM2 overexpression and subsequent p53 degradation. Further investigations revealed that targeting NAT10 with Remodelin showed anti-cancer activity in GC and augmented the anti-tumor activity of MDM2 inhibitors in p53 wild-type GC. These results suggest the critical role of NAT10-mediated ac4C modification in GC oncogenesis and reveal a previously unrecognized signaling cascade involving the Hp-NAT10-MDM2-p53 axis during GC development.